2022
DOI: 10.2186/jpr.jpr_d_21_00343
|View full text |Cite
|
Sign up to set email alerts
|

Expected and perceived burdens in patients receiving mandibular overdentures retained by one or two implants

Abstract: Multiple factors may influence edentulous patients' intentions and behaviors toward oral rehabilitation, including their perceptions of costs, opportunity costs, perceived needs, and access to dental care [1]. However, another relevant aspect of adherence to treatment is how patients perceive the burdens associated with treatment. 'Treatment burdens' may be defined as both the workload and impact of treatment regimens on the function and well-being of patients [2]. These can produce significant negative impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Knowing what patients' expectations are and whether they are fulfilled after treatment is important for improving patient‐centred care and satisfaction 37 . In contrast to previous studies, we included patients treated with different dental prostheses and found that expectations of fixed and removable dental prostheses were fulfilled.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing what patients' expectations are and whether they are fulfilled after treatment is important for improving patient‐centred care and satisfaction 37 . In contrast to previous studies, we included patients treated with different dental prostheses and found that expectations of fixed and removable dental prostheses were fulfilled.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant considering the concept of simplifying treatment and reducing the number of implants. Indeed, despite a largely accepted consensus of two implants as a requirement for the stabilization and retention of a complete mandibular denture, low economic resources, as well as reluctance to invasive surgical procedures still challenge this established treatment option (Feine et al, 2002; Garcia et al, 2022; Thomason et al, 2012). IODs retained by a single midline implant (1‐IOD) have been proposed as a more conservative and less costly alternative to the standard 2‐IOD (Bhat et al, 2016; Bryant et al, 2015; Hartmann et al, 2020b; Nogueira et al, 2017; Passia et al, 2019; Schwindling et al, 2018; Srinivasan et al, 2016; Walton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, minimizing the number of hospital visits using digital workflow and accomplishing treatment as simply as possible is necessary [1,2]. In addition, as a minimally invasive treatment that exhibits potent effects despite a low cost, implant overdenture, is very effective for fully edentulous patients [3][4][5].…”
mentioning
confidence: 99%